Evaluación del efecto antifúngico in vitro de una crema de plantago major en cepas de candida albicans” - Mozombite Asmat, Carlos Adrian Wagner (2009)
Candida is a dimorphic fungus of worldwide distribution that is part of the resident flora of the mouth, digestive and female genital tract of healthy subjects. Under some conditions, for reasons that are sometimes well-established and in some cases not well known, could be responsible for high-risk conditions and sometimes fatal. They can cause damage to skin, nails, oral cavity, bronchi, lungs and reach all the organs and blood systems through propagation of yeast, which is called fungemia or candidemia. The increase in yeast infections is a growing phenomenon worldwide, and Peru is no exception to this problem. The antifungal treatment has been enhanced recently with new preparations are improving treatment options for many patients. The experimental determinations of this study give us some hope in a possible alternative to antifungal therapy for Candida albicans. It was demonstrated by an in vitro study, according to the disk diffusion method in Sabouraud, the antifungal effect of a cream made from the leaves of Plantago major in a concentration of 18.5 g of solids per gram of cream, it was very effective Candida albicans versus the inhibition halos produced by the cream of Plantago major L., nystatin and ketoconazole 2% in strains of Candida albicans, there is a difference between their diameters minina, which are 0.15 ± 0.05 mm. and 0.32 ± 0.05 for cream of Plantago major - Ketoconazole 2% cream and cream of Plantago major L. - Nystatin. The percentage inhibition of the cream of Plantago Major L. halt to the drugs (ketoconazole 2% and Nystatin) is 95.63% and 99.06%, which indicates a good antifungal effect, the statistical analysis of data obtained in the experiment, with a significance value of 0.95 and with a P value <0.05; was obtained a P value> 0.05, which indicates not significance between antifungal creams used for the placing under evaluation.